Comprendiendo el cuidado de los ancianos en situación de discapacidad y pobreza (2009)
Este es un estudio cualitativo dirigido a comprender el contexto ambiental y la trayectoria de cuidado popular de las personas ancianas en situación de discapacidad y pobreza que habitan en cinco barrios de los cerros nororientales ubicados en Bogotá. Se usó la teoría de la diversidad y universalidad del cuidado (Leininger) y el modelo de cuidado en la adversidad (López Díaz). Como metodología se utilizó la etnografía de tipo interpretativo y los datos fueron recolectados mediante observación participante y entrevistas en profundidad. En el análisis emergieron dos temas culturales: 1) “Viviendo en un valle de lágrimas: entre la resignación y la lucha de vivir en la vejez, la discapacidad y la pobreza”, que muestra cómo estas personas enfrentan un contexto complejo y adverso, expresado en una cadena de sucesos que han experimentado toda su vida, y 2) “Descubriendo los caminos del cuidado popular de las personas ancianas en situación de discapacidad y pobreza”, en el que se revelan diversas posibilidades para generar una alternativa de cuidado de estas personas. Emerge la manera como estas personas buscan cuidar su salud a partir de su contexto ambiental, su cultura y sus necesidades, configurando un cuidado popular integrado en una trayectoria intangible, pues no se limita a la realización de acciones instrumentales: ellas tienen de fondo una lógica en donde se evidencia la comprensión de su situación actual , se identifican diversas condiciones que permiten la toma de decisiones y, finalmente, se visibilizan los actores que intervienen en el cuidado y las prácticas heredadas culturalmente como mezcla de distintos saberes cambiantes y dinámicos. / Abstract. This is a qualitative study which objectives were as follows: To understand the environmental context of elders in situation of disability and poverty. They are inhabitants of five neighborhoods of the north eastern hills located in the city of Bogota D.C. As a theoretical reference, the diversity and universality in care developed by Madeleine Leininger and the care model in adversity were used as part of the conceptual framework used for developing of this sub-line of research in trans-cultural, geronto – geriatric nursing, which emerged from one of the studies made by Lopez Diaz with elders in urban, marginal areas of Sao Paulo, Brazil, and Bogota, Colombia. An interpretative ethnography procedure was performed with elders in situations of disability and poverty. Data were collected by participant observation and deep interviews. Analysis was done by following Leininger proposal. In such a way, two cultural topics arose: “Living in the Valley of Tears: between the acceptance and the fight for living in elder times within disability and poverty”, which shows how those people face a context loaded with difficulties and all a series of adverse situations. Such situations constitute the links of a chain of events experimented throughout all their lives. The second cultural topic, “Discovering pathways in popular care for elders in situation of disability and poverty”, in which the author presents several options and situations making possible the generation of a way for giving care to those people. It is evident the way, these people seek to look after their health from their environmental context, their culture and their needs; in this manner, they configure a popular care. Such a type of care is integrated into an intangible trajectory, because it is not limited to the performance of instrumental actions: they have in the background certain logics, where it is visible the understanding of the situation of health. It is identified a series of conditions allowing the making of decisions. Finally, the actors intervening in care and culturally inherited practices are visible, which are a mix of several changing and dynamic ways to know.